Development of Cadets Worksheets based on Problem Centered Learning as Applied Physics Learning Media - Nelfi Erlinda; Budi Rianto; Dody Efrianto (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2018)
The purpose of this study to develop valid and practical Cadets Worksheets based on Problem Centered Learning. This type of research was a Research and Development (R & D) research, which uses six research steps: potential problems, information gathering, product design, design validation, design improvement, and testing. The research instrument used was a questionnaire of validity and questionnaire of practicability. Analysis techniques used to test the validity and practicality of learning materials developed student worksheet was Likert-scale analysis techniques. Based on validation data analysis by validator obtained average percentage value of Cadets Worksheet was 83,6% (very valid). The result of Cadets Worksheet practice percentage by students' was 83.4% (very practical). Based on the above data analysis can be concluded that Worksheet Physics based PCL developed valid and practical.